Teaching the Holy Qur'an using imaginative arts and its effect on creative thinking : an experimental study in a Saudi school, Malaysia - Asmri, Sarah Ali M (Kulliyyah of Education, International Islamic University Malaysia, 2015)
This study focuses on the effect of using imaginative arts in teaching the Holy Qur'an on creative thinking at the Saudi School in Kuala Lumpur, Malaysia. The sample for this study consisted of 40 second grade students in the school. They were divided equally into two groups of 20 each for the experimental and control group respectively. The researcher used the quasi-experimental research design in the investigation. In particular, the study investigated the effect of the imaginative arts on the students' creativity in figural dimensions namely; fluency, flexibility, originality and elaboration. The Torrance test of Figural Dimension was applied to obtain the scores for each of the dimension. The independent sample t-test was used to examine the difference of the pre and posttest scores. The regression analysis was applied to investigate the effect and the relationship of the control and experimental group. The results of the tests showed that teaching the Holy Qur'an using imaginative arts has no strong effect on the respondents' figural fluency and flexibility. The results also showed that there were no statistically significant differences between the pre and posttest of the experimental group with respect to fluency and flexibility. On the other hand, there were statistically significant differences in originality and elaboration between the pre and posttest of the experimental group. Based on these findings, it is suggested that Qur'anic teacher should apply different and effective methods of teaching the Holy Qur'an and not only focus on students' memorization ability. Qur'anic teachers should apply a variety of methods including imaginative arts so as to assist in the goal of memorization as well as to enhance their creativity.